The Quranic Theory of Education: Methodological Reflections - Nakib, Omar (Jurnal Usuluddin, 2017)
This study is an investigation into the components of the methodological approach that must be adopted to tackle the Quranic theory of education. The purpose is to suggest some methodological requirements to approach such a theory in a form of a methodological framework that may enable us to elaborate the components of a new Islamic theory of education. The study involved an investigation into the exegesis of Al-Qur’ān verses. Qualitative methodology was adopted, and content analysis was employed to examine the related data. Three questions have been addressed: Does Al-Qur’ān involve a theory of education? What are the required methodological considerations to address the Quranic model of education as prescribed in Al-Qur’ān? What are the methodological requirements necessary to formulate the Quranic Model of Education? The findings show that Al-Qur’ān has prescribed a set of educational teachings as a methodological framework that must be considered whenever there is an attempt to unveil the revealed Quranic theory of education. To conclude, it is recommended to observe such methodological requirements to adequately unveil the essential features of the Quranic model of education. This is to pave the way for Muslim educational practitioners to actualize the meanings of the desired model of man as prescribed by Al-Qur’ān in their educational practice.